The Bargmann type reduction for some Lax integrable two-dimensional generalization of the relativistic Toda lattice - Hentosh, O.Ye. (Carpathian Mathematical Publications, 2015)
The possibility of applying the method of reducing upon finite-dimensional invariant subspaces, generated by the eigenvalues of the associated spectral problem, to some two-dimensional generalization of the relativistic Toda lattice with the triple matrix Lax type linearization is investigated. The Hamiltonian property and Lax-Liouville integrability of the vector fields, given by this system, on the invariant subspace related with the Bargmann type reduction are found out.